Aspekte van gen. 1-3 en die natuurwetenskappe - Heiberg, J. L. (Koers, 1988)
This article wishes, from the angle of the subject of Revelation History, to offer thoughts and ideas about aspects touching on the shared issues of the various disciplines. The special nature of the material and of the purpose of Genesis 1 ff. does not necessarily imply that a closed suc cession of days is meant. God is the Creator and the Ruler over all things, and has a historical destiny for the earth. Man is the steward over creation, has an ecological task and is in that responsible to God. He is in a communational relation to God, and is free from the enslavement of a combination of natural and spiritual forces. There is a special re lation between man and beast, but there is no question of a communational relation there, only with God, of whom man is the image. Sin corrupted the relation between man and creation, but Genesis 2, 3 already stand in the sign of the expectation of restoration. There is a universal basis for the practice of scholarship, and at the same time the shaping demand is that knowledge begins with the service of God.